Organizational Culture as the Foundation for the Formation of Work Ethic - Muhammad Al Fatih (CV. Agrapana Media, 2026)
Educational institutions continue to face low educator work ethic, reflected in poor discipline, inadequate preparation, and weak responsibility, which are largely influenced by an underdeveloped organizational culture that hampers the internalization of professionalism and ultimately affects education quality. This study aims to examine organizational culture as the foundation for the formation of work ethic in educational institutions. The research employs a qualitative approach using a library research method. Research data were obtained from various written sources, including textbooks, scientific journal articles, and previous studies relevant to organizational culture and work ethic in education. Data collection was conducted through systematic literature searching, selection, and classification, while data analysis was conducted using content analysis with a descriptive-analytical approach. The results of the literature review indicate that organizational culture plays a crucial role in shaping the attitudes, behaviors, and work commitment of educators and educational staff. Cultural values such as discipline, responsibility, professionalism, and integrity are identified as the core foundations in developing a strong work ethic. Furthermore, leadership that is consistent with organizational cultural values strengthens the internalization of work ethic within educational environments. The theoretical synthesis confirms that a strong work ethic does not emerge instantly but is formed through a positive and sustainable organizational culture. This study concludes that strengthening organizational culture is a strategic effort to enhance work ethic and improve the quality of education